A profile-based peer-to-peer RSS information distribution - Baumgart, André; Knapp, Hartwig; Suetterlin, Pascal; Schader, Martin (2nd International Symposium on Wireless Pervasive Computing, 2007, 2007)
Really simple syndication (RSS) is an XML dialect that is widely used to distribute personalized information. From the user's perspective, RSS seems to be the ideal news reader technology because the RSS feeds notifies the user of information updates. In this paper we propose a profile-based peer-to-peer RSS information distribution for mobile devices using RSS feeds. We show how peers connect with each other and explain the mapping of user keywords with existing RSS feeds on other peers effectively. We have implemented a prototypical application and introduce the most important features